In the Mind of the Ophthalmology Residency Applicant: Deciding Where to Apply, Interview, and Rank - Jin, Joy Q.; Ahmad, Tessnim R.; Parikh, Neeti; Srikumaran, Divya; Woreta, Fasika; Ramanathan, Saras (Journal of Academic Ophthalmology, 2022)
Objective This article characterizes the resources used by ophthalmology residency applicants when deciding where to apply, interview, and rank.Design Cross-sectional, online survey.Participants All applicants to the University of California–San Francisco ophthalmology residency program during the 2019 to 2020 and 2020 to 2021 application cycles.Methods A secure, anonymous, 19-item post-match questionnaire was distributed to participants inquiring about demographic information, match outcomes, and resources used to learn and make decisions about residency programs. Results were analyzed using qualitative and quantitative methods.Main Outcome Measures Qualitative ranking of resources used to decide where to apply, interview, and rank.Results One hundred thirty-six of 870 solicited applicants responded to the questionnaire, for a response rate of 15.6%. Digital platforms were ranked as more important resources than people (i.e., faculty, career advisors, residents, and program directors) when applicants were deciding where to apply and interview. Digital platforms became far less important when applicants were formulating their rank lists, at which time the program's academic reputation, perceived happiness of residents and faculty, interview experience, and geographic location were more important. When learning about residency programs, 100% of respondents engaged with program Web sites, and the majority engaged with program emails (n=88 [85.4%]), Doximity (n=82 [79.6%]), Reddit (n=64 [62.1%]), Instagram (n=59 [57.3%]), the FREIDA residency program database (n=55 [53.4%]), and YouTube (n=53 [51.5%]). All 13 digital platforms included in the survey were utilized by at least 25% of respondents, largely passively (i.e., reading rather than producing content). Respondents indicated that the most important topics to include on program Web sites were the number of residents accepted per year, current resident profiles, and resident alumni job/fellowship placement.Conclusion Applicants engage heavily with digital media in deciding where to apply and interview but rely heavily on their personal experiences with the program in deciding where to rank. Ophthalmology programs may facilitate recruitment of applicants by optimizing their digital media platforms.
Keywords: ophthalmology; applicant; residency; medical student; digital media; decision-making; information gathering